2014
DOI: 10.1111/pcn.12251
|View full text |Cite
|
Sign up to set email alerts
|

Increased prefrontal hemodynamic change after atomoxetine administration in pediatric attention‐deficit/hyperactivity disorder as measured by near‐infrared spectroscopy

Abstract: Aim: Atomoxetine, approved in Japan for the treatment of pediatric attention-deficit/hyperactivity disorder (ADHD) in April 2009, is a nonstimulant that is thought to act presynaptically via the inhibition of norepinephrine reuptake. Near-infrared spectroscopy is a non-invasive optical tool that can be used to study oxygenation and hemodynamic changes in the cerebral cortex. The present study examined the effects of a clinical dose of atomoxetine on changes in prefrontal hemodynamic activity in children with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Risk factors include familial stressors, physical and psychological and sexual child abuse, anxiety disorders, learning disabilities, abnormal brain development, heritability, and dopamine polymorphisms [6]. Mother hyperemesis gravídarum, oligohydramnios and loss of amniotic fluid, abnormal uterine bleeding during pregnancy, as reported in the present study has not been related thus far as risk factors for child attention deficit.…”
Section: Risk Factorssupporting
confidence: 45%
“…Risk factors include familial stressors, physical and psychological and sexual child abuse, anxiety disorders, learning disabilities, abnormal brain development, heritability, and dopamine polymorphisms [6]. Mother hyperemesis gravídarum, oligohydramnios and loss of amniotic fluid, abnormal uterine bleeding during pregnancy, as reported in the present study has not been related thus far as risk factors for child attention deficit.…”
Section: Risk Factorssupporting
confidence: 45%
“…In an NIRS study of medication, Ota et al examined the effects of a clinical dose of ATX on changes in prefrontal hemodynamic response during the Stroop color-word task in pediatric ADHD. They found that ATX induced an intensified prefrontal hemodynamic response [31]. In another NIRS study, Araki et al found that the oxy-Hb concentration in the right dorsolateral PFC in the post-ATX condition was significantly increased compared to the pre-ATX condition during a continuous performance task [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NET is suggested to play a critical role in ADHD Ota et al [24]. Recent studies have shown that ADHD is characterized by multiple functional and structural neural network abnormalities including most prominently fronto-striatal, but also fronto-parieto-temporal, fronto-cerebellar and even fronto-limbic networks Castejon et al [25] Evidence from longitudinal structural imaging studies has shown that ADHD is characterized by a delay in structural brain maturation Rubia et al [26].…”
Section: Discussionmentioning
confidence: 99%